Astra honda motor company reaction to viral complaints about honda motorcycle esaf frames - George Wilhelm Bender (Jurnal Scientia, 2024)
Astra Honda Hotor, and is embedded in several motorbikes with automatic transmissions. It is claimed to be simpler and lighter; the ESAF frame is also more robust and has minimal deformation, increasing luggage capacity and fuel efficiency. However, it is not surprising that several users indicated that there were weaknesses in the frame, ranging from rust to breaking and folding into two parts. With the high penetration of internet users and the massive number of social media users, this has no doubt made the case of the eSAF frame go viral because it is often found on social media, starting from TikTok, Instagram, or Facebook, where users post videos of the Honda motorbike's eSAF frame being damaged. The rust broke on the road even though it had only been purchased a few months until a petition emerged to recall Honda motorbikes with eSAF frames. This research aims to describe the reaction of PT AHM, as the holder of the Honda motorbike brand, to activities on social media regarding the eSAF frame case for Honda automatic transmission motorbikes.